The Finnish style of international business negotiations : The impact of generations X, Y and Z - Zenad, Samir (My University, 2021)
The ongoing globalization is increasing the international business and raising the value of business contracts. The need for competent global negotiators will turn the eyes to the next generation Z. The objective of this thesis is to investigate the role of generations X, Y and Z on the negotiating tendencies of Finnish negotiators involved in international business. The topic is new and there is substantial need to research this field. Theoretically the thesis leans on the work of Jeswald Salacuse whose 10 negotiation elements form the measured and studied variables. Methodologically the study falls into the research philosophies of positivism and critical realism. It does not present law-like generalization but increases the knowledge of the research area and aims to fill some part of the existing research gap. The research approach is deductive. The empirical part of the study was collected via e-mail survey from 141 respondents and the statistical program SPSS was used to analyze the data. The results show significant differences between Finnish generations X, Y and Z members across nine out of ten negotiation elements. Extremely strong significant differences between generations X, Y and Z are found for the negotiation goal, personal style, time sensitivity, agreement form, team organization and risk taking. A very strong significant difference is found for communication style, and a strong significant difference is found for agreement building. However, no significant difference was found for attitude element. This thesis achieved its aim to increase the knowledge of Finnish generation Z business negotiation behaviour. However, the research sample was limited, and the generation Z international business negotiation styles should be studied across different cultures and countries in the future research. The interest to understand the mindset of the young generation that is entering to companies is but academic also managerial.
Keywords: negotiations; business; Finland; culture; intercultural communication; attitudes; generations; agreements; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business